A Modified Climate-Smart Push-Pull Technology for the Management of Fall Armyworm (Spodoptera frugiperda) in the Semiarid Lands of Kenya - Mumo, Catherine Kuthea; Muturi, Phyllis W.; Gichimu, Bernard M. (University of Embu, 2024)
Successful use of push-pull technology in the control of fall armyworm (Spodoptera frugiperda Smith) in maize has been limited to areas that receive optimal rainfall as opposed to the semiarid areas. This study sought to determine the viability of a modified push-pull technology designed for drier areas. The technology involved the use of the drought-tolerant Brachiaria grass as a potential replacer of Napier grass as a pull crop, alongside drought-tolerant green-leaf Desmodium (Desmodium intortum) and edible legumes as push crops. The study was conducted in Mbeere South Subcounty in Embu County, Kenya. The experiments were laid out in split plots arranged in a randomized complete block design with three replications. The main plots contained Napier and Brachiaria grasses as comparative pull crops while the subplots tested the performance of the drought-tolerant green-leaf Desmodium and edible legumes (cowpea, pigeon pea, and green gram) as push crops. A maize monocrop was used as the negative control. The pest dynamics were determined using the area under damage/pest curve (AUDPC). The highest pest incidence was observed in the maize monocrop treatments with AUDPC range of 64–65.5 as compared to the intercrop treatments with AUDPC range of 45–56. The AUDPC for damage severity ranged from 24 to 24.5 in the maize monocrop treatments and 15.5 to 18.7 in the intercrop treatments. These findings implied that the drought-tolerant green-leaf Desmodium and the edible legumes can be adopted as effective push crops in the modified push-pull technology. Brachiaria and Napier grasses portrayed similar suitability as pull crops implying that the two can be used interchangeably as pull crops based on farmers’ preference. This study confirmed the viability of the modified climate-smart push-pull technology in the management of fall armyworm in dryland areas.